EFFECTIVENESS HEALTH EDUCATION USE SPEECH AND DISCCUSION METHODS CONCERNING ON NARCOTIC DANGER FOR STUDENTS OF 9TH CLASS IN SMP N I BANYUDONO - Kustati, Ari; Aryani, Atik; Bintoro, Wahyu (JURNAL ILMU KEPERAWATAN INDONESIA (JIKI), 2016)
Background :There is 4 million people (2.18%) of Indonesian are narcotic user population 10-59 years old, from 4 million there are 1.6 million are trial stage, 1.4 million are user and 943 million are dope addict. Depend on wsriter?s interview with teacher of SMP N I Banyudono, at this school was given narcotic counseling for students. But measuring of narcotic knowledge doesn?t reported and from early survey from 10 students of 9th class, 5 students are have good knowledge about narcotic and the denger, 3 students know enough and 2 others was less. Purpose : To know about effectiveness health education use speech and discussion methods conserning on narcotic danger for students of 9th class in SMP N I Banyudono. Metods : This research used Quasy Experimental Design. The approached Method was pretest-postest design. The population of the research were students of 9th Class SMP N I Banyudono which amount 217 students consisted of 7 class, sampling technique use simple random sampling with the sample of the 31 students. The analysis of data used paired T Test. Results : The result of statistic research, increased of mean value on speech methods with t sampling pair was 15.81%, group used disscusion methods increased 19.73%. The conclusion was effectiveness of increasing students knowledge used disscuion methods was larger than speech methods. Summary : Health education about the danger of narcotic must be continued and given early to prevent abuse of narcotic on teenagers.